Prophetic Communication in Child Protection: Strategies of the Indonesian Child Protection Agency in Preventing and Addressing Violence against Children - Azhari Harahap; Nispul Khoiri; Ahmad Sampurna (KURAS Institute, 2025)
Child protection remains a critical issue in Indonesia, with rising cases of violence against children. This study examines the implementation of prophetic communication by the Indonesian Child Protection Agency in South Labuhan Batu as a strategy to prevent and address child abuse. Utilizing a qualitative descriptive approach, data were collected through in-depth interviews, participatory observation, and document analysis involving LPAI staff, volunteers, psychologists, and religious leaders. Data validity was maintained through triangulation of sources and methods, in-depth field involvement, and peer debriefing.The findings reveal that prophetic communication grounded in the principles of ‘amar ma’rūf (promotion of good), nahimunkar (prevention of harm), and ta’lim/tazkiyah (transcendence and moral development) effectively combines religious, moral, and social dimensions with modern communication strategies. Key supporting factors include skilled human resources, community and government support, and multi-stakeholder collaboration, while challenges involve cultural norms normalizing violence, limited resources, and trauma-related barriers. The study underscores the importance of empathetic, culturally-sensitive, and trauma-informed communication in child protection programs. Implications for policy, practice, and future research are discussed, emphasizing the potential for scaling prophetic communication.